Konsep desain dan perbaikan produk Ankle Foot Orthosis menggunakan metode kansei engineering - Suhendrianto Suhendrianto; Sarika Zuhri; Hafidzah Andra Nalimaruscha Tarigan; Asbar Asbar (Politeknik Negeri Lhokseumawe, 2021)
Stroke is a non-infections disease that can cause death. The impact of stroke is leg muscles getting weaken so leg cannot be used normally. This condition occurs due to leg muscles are not frequently used and the experience a decrease in muscle mass as a result of the stroke condition. Foot that cannot be used normally can be treated by doing therapy and wearing an ankle foot orthosis (AFO). AFO is an orthopedic aid that is attached to the foot. The benefits of AFO are to improve the structure of the legs and help users to return to walking normally. This research was conducted to redesign AFO by identifying customer need and emotions towards AFO products through the Kansei Engineering method. The study was conducted by distributing 12 pairs of Kansei questionnaires up to 20 respondents through a quota sampling technique. The results were analyzed using multivariate statistics. The data processing used to compile the design element questionnaire. This questionnaire combines two categories for each design item. Respondents can choose which the best design combination. The selected design parts are open design with webbing tight type, the selected material is combination of plastic and steel, and the unobtrusive color. The design result is used as a reference for AFO design and manufacture.